2008
DOI: 10.1016/j.dnarep.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Mutations to Ku reveal differences in human somatic cell lines

Abstract: NHEJ (non-homologous end joining) is the predominant mechanism for repairing DNA doublestranded breaks in human cells. One essential NHEJ factor is the Ku heterodimer, which is composed of Ku70 and Ku86. Here we have generated heterozygous loss-of-function mutations for each of these genes in two different human somatic cell lines, HCT116 and NALM-6 using gene targeting. Previous work had suggested that phenotypic differences might exist between the genes and/or between the cell lines. By providing a side-by-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 52 publications
4
41
2
Order By: Relevance
“…28,29). Similarly, targeting efficiency, which is mediated by HR, is increased in a dose-dependent manner (51). We have suggested that differing requirements for DNA-PK levels in humans may reflect a more stringent requirement to regulate HR at hyper-recombinogenic genomic regions (30,52).…”
Section: Figurementioning
confidence: 89%
“…28,29). Similarly, targeting efficiency, which is mediated by HR, is increased in a dose-dependent manner (51). We have suggested that differing requirements for DNA-PK levels in humans may reflect a more stringent requirement to regulate HR at hyper-recombinogenic genomic regions (30,52).…”
Section: Figurementioning
confidence: 89%
“…In contrast, human cell lines with inactivated KU70 or KU80 are not viable, which suggests that KU70 and KU80 are essential for human cell viability (53,54). Xrcc4-deficient mice are embryonic lethal due to apoptosis of postmitotic neurons (55), and if this can be extrapolated to humans, functional null mutations in XRCC4 are also unlikely.…”
Section: Ku70- and Ku80-knockout Mice Are Viable And Have An Rs-scidmentioning
confidence: 99%
“…The structural components of the core NHEJ complex, KU70 and KU80, are essential for human cell viability [24,25] and there are no documented patients with mutations in these proteins. Other components of the NHEJ complex (DNA-PKcs, Lig4 and XLF/Cernunnos) are also likely to be essential for development, although patients carrying hypomorphic mutations in these proteins have been reported [26][27][28].…”
Section: Introductionmentioning
confidence: 99%